A qualitative analysis of free text comments of participants from a massive open online mindfulness course - Neate, Sandra L.; Reece, Jeanette C.; Hassed, Craig; Chambers, Richard; Connaughton, Sherelle; Nag, Nupur (Frontiers in Public Health, 2022)
Introduction: Mindfulness-based interventions are associated with improved health and wellbeing. Online mindfulness interventions offer potential scalability and cost advantages over face-to-face interventions. However, little is known about the experiences of learners, what they identify as being helpful to developing a practice of mindfulness and what outcomes they experience from undertaking an online mindfulness program. Methods: The Mindfulness for Wellbeing and Peak Performance Massive Open Online Course is a four-week mindfulness program which includes psychoeducation, mindfulness meditation, applications and moderated discussion forums. Of the 3,335 participants who completed the March 2020 course, 527 (16%) responded to the final forum which invited participants to describe the highlights of the course. In order to enhance understanding of participant experiences and perceived outcomes of undertaking the course, a qualitative analysis of these free text comments was conducted using reflexive thematic analysis. Results: Two overarching themes were identified: (1) internal mechanisms of developing mindfulness (subthemes: paying attention to the present moment, learning to let go and find acceptance, cultivating an attitude of gentleness, and learning through a sense of belonging) and (2) the translation of mindfulness into daily living (subthemes: mindfulness being a support to mental wellbeing, learning to deal with uncertainty and adversity, living a more conscious life, a greater connection with self and others and channeling attention into productivity). Discussion: The themes and subthemes provided insights into the mechanisms learners used to develop mindfulness and how they translated mindfulness into their lives in a variety of beneficial ways. This understanding of learners’ experiences could inform delivery of future online mindfulness interventions.